Design-Based Research (DBR): A Socioconstructivist and Investigative Proposal for Learning about Heredity and Reproduction in Secondary Education (Práxis Educativa, 2025)
In the field of science education, addressing students’ spontaneous ideas is key to promoting meaningful learning. This study is framed within a socioconstructivist and inquiry-based approach and aims to analyze the impact of an Investigative Teaching Unit (ITU) on heredity and reproduction in the learning of secondary school students. The intervention was developed through Design-Based Research (DBR) and implemented in an educational center in Seville, Spain, with a sample of 29 students. Based on an initial questionnaire to explore students’ ideas, content, problems, and activities were designed to support the development of those ideas. Formative assessment made it possible to identify significant learning progressions. The results, represented through learning ladders, highlight the potential of the approach to transform students’ initial conceptions, strengthen their scientific literacy, and promote a form of teaching that is connected to real-life contexts.Keywords: Heredity and Reproduction. Design-Based Research (DBR). Students' Ideas.